2016
DOI: 10.3390/su8050493
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Perceptions of Corporate Social Responsibility and Job Performance: A Sequential Mediation Model

Abstract: Abstract:In spite of the increasing importance of corporate social responsibility (CSR) and employee job performance, little is still known about the links between the socially responsible actions of organizations and the job performance of their members. In order to explain how employees' perceptions of CSR influence their job performance, this study first examines the relationships between perceived CSR, organizational identification, job satisfaction, and job performance, and then develops a sequential medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 61 publications
5
102
0
4
Order By: Relevance
“…Furthermore, in a strategic approach to CSR, where social and business objectives are aligned, and where social initiatives are related to the main activity of the implementing business organisations, CSR programs dedicated to employees can provide significant benefits in a win-win perspective. As previously noticed, past research has tended to neglect the implications of CSR activities on the employee's professional performances, while it can be proven that CSR can play a pivotal role in employees' identification with the employer and job satisfaction, and thus to job performance [5].…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, in a strategic approach to CSR, where social and business objectives are aligned, and where social initiatives are related to the main activity of the implementing business organisations, CSR programs dedicated to employees can provide significant benefits in a win-win perspective. As previously noticed, past research has tended to neglect the implications of CSR activities on the employee's professional performances, while it can be proven that CSR can play a pivotal role in employees' identification with the employer and job satisfaction, and thus to job performance [5].…”
Section: Introductionmentioning
confidence: 95%
“…Since the main reason for an organization's CSR activities is not to facilitate the productive outcomes of its members or to restrain their counterproductive outcomes [18], it is difficult for us to believe that perceived CSR is likely to have a direct influence on their CWB. To investigate how and why employees' perceptions of CSR are related to their CWB, the current study relies on the stimulus-organism-response model that has been widely used to explain the mechanisms and reasons that stimuli and responses are related, and to identify the fundamental processes underlying the relationship between organizational contexts and individual behavior [20].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is well known that the degree to which employees perceive whether their organization participates in CSR activities and policies contributes to organizational effectiveness by promoting their outcomes [13][14][15]. Indeed, numerous studies have demonstrated that employees' beliefs about their organization being socially responsible exert influence over a variety of their outcomes, including job satisfaction, employee engagement, organizational identification, and job performance (e.g., [16][17][18][19]. Even if the significant effects of perceived CSR on employees' attitudes and behaviors lead us to expect that it has sufficient potential to determine their levels of CWB, there is little information regarding how perceived CSR is actually associated with CWB.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability impacts the economy in three ways: (1) it has a direct effect through energy savings; (2) it has an indirect effect because an environmentally friendly image creates a competitive advantage; and (3) the business gains the advantage of being positioned as a green company [14][15][16][17][18][19][22][23][24][25][26][27][28]. To a lesser extent, previous research has found that there is a social impact [2,11] and an impact on the acquisition of unique capabilities [2,29,30].…”
Section: Evolution Of Eco-innovationmentioning
confidence: 99%